Prioritetnye nauchnye issledovaniya kafedry lyzhnogo sporta SGIFKa - Ermakov, V. V.; Kobzeva, L. F. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The analysis of over 35 years-long SSIFC skiing faculty's scientific path is represented in the article. The authors noted the main trends of the faculty's scientific searching: structure of motions, technical specifics, variations and durability of motor structure, modeling, rationalization and optimization of motor actions, training methods' efficiency estimation. Besides that, the authors noted some faculty's scientists, which had win the wide recognition in Russia. Some scientific successes of the faculty are noted also.